2023
DOI: 10.3389/fimmu.2023.1128582
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting endocytosis for transfection of mRNA for cytoplasmatic delivery using cationic gold nanoparticles

Abstract: IntroductionGene therapy holds promise to cure various diseases at the fundamental level. For that, efficient carriers are needed for successful gene delivery. Synthetic ‘non-viral’ vectors, as cationic polymers, are quickly gaining popularity as efficient vectors for transmitting genes. However, they suffer from high toxicity associated with the permeation and poration of the cell membrane. This toxic aspect can be eliminated by nanoconjugation. Still, results suggest that optimising the oligonucleotide compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…Much of the early work on inorganic nanoparticles focused on siRNA bound onto gold, silica, and iron oxide, , extended more recently to mRNA and to zinc oxide and other metal nanoparticles. , Ironically despite early work on nonzinc-based systems, zinc (Zn) is perhaps best known for its role in stabilizing nucleic acid interactions in cells and tissues, and thus early on, we focused on its effects on cell viability to cells in culture, its RNA interaction and to antisense oligomer and aptamer. ,, With great interest in RNA-based medicine, it was important to extend this to macromolecular RNA, and initially we used torula yeast (TY-RNA), which can be obtained in bulk for formulation studies and when purified gives a homogeneous band on gel analysis in the approximate molecular weight range of mRNA (Figure S1). As a next step, we demonstrated the association of cationic peptide and RNA to the surface ZnO NP (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the early work on inorganic nanoparticles focused on siRNA bound onto gold, silica, and iron oxide, , extended more recently to mRNA and to zinc oxide and other metal nanoparticles. , Ironically despite early work on nonzinc-based systems, zinc (Zn) is perhaps best known for its role in stabilizing nucleic acid interactions in cells and tissues, and thus early on, we focused on its effects on cell viability to cells in culture, its RNA interaction and to antisense oligomer and aptamer. ,, With great interest in RNA-based medicine, it was important to extend this to macromolecular RNA, and initially we used torula yeast (TY-RNA), which can be obtained in bulk for formulation studies and when purified gives a homogeneous band on gel analysis in the approximate molecular weight range of mRNA (Figure S1). As a next step, we demonstrated the association of cationic peptide and RNA to the surface ZnO NP (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we patented a cationic peptide-coated particle approach to load the DNA vaccine and provide the stability necessary for clinical translation . That work involved gold particles that are nonphysiologically based, and, unfortunately, nanoscale gold must be chemically derivatized to load siRNA and for which relatively little mRNA work has thus far been reported . Although there have been some physiologically based inorganic and surface-coated nanoparticles, thus far, the few reports of their RNA surface absorption, RNA temperature stabilization, and RNA delivery are relatively modest. The majority of clinical work thus far has focused on iron oxide nanoparticles, none of which has yet been extended to RNA with one noteworthy preclinical example for miRNA .…”
mentioning
confidence: 99%
“…Singh团队 [11] 开发了叶酸(folic acid, FA)修饰的聚胺生 成-5(PAMAM G5D)接枝的球状金纳米粒子, 并使用荧 光素酶报告基因(Fluc mRNA)在体外评估了其细胞毒 性和表达效率. Puntes团队 [88] 开发了一个包含不同尺 寸AuNP核和两种不同阳离子分子功能化的纳米载体 库, 负载mRNA, 用于非病毒转染载体的应用. SeNPs是…”
Section: 蛋白/多肽递送载体unclassified
“…The clinical applications of RNA drugs are primarily limited by the delivery issue: the lack of efficient carriers for delivering RNA molecules to target cells and tissues [98]. Several studies have shown the unsatisfactory efficacy of delivering naked mRNA [99,100], which is caused by the high rates of RNA degradation during its circulation, RNA-induced innate immunity, and poor cellular infiltration [35,86,101].…”
Section: Mrna Delivery System: Exosomes and Lnpsmentioning
confidence: 99%